Chlamydia trachomatis pORF5 plasmid-encoded protein regulates autophagy and apoptosis of HeLa cells. Issue 1 (1st January 2019) - He, Bei; Zhao, Yuqi; Yang, Xiaoyu; Su, Shengmei; Wen, Yating; Chen, Hongliang; Zhou, Zhou; Huang, Qiulin; Li, Zhongyu
Abstract: Chlamydia trachomatis is an important human pathogen responsible for a variety of important diseases. pORF5, a plasmid protein in C. trachomatis, has been reported to contribute to chlamydial pathogenesis. Apoptosis and autophagy are two important cellular processes, which also participate in the pathological and the physiological processes in C. trachomatis infection. The present study aimed to explore the effects of pORF5 protein on autophagy and apoptosis in HeLa cells. Stable pORF5-HeLa and vector-HeLa cell lines that were transduced with pORF5 recombination lentivirus and control lentivirus, respectively, were constructed. Immunofluorescence was used to observe the cells. Western blotting was carried out to detect expression of target proteins. Real-time polymerase chain reaction was used to determine the mRNA expression. Flow cytometry, TUNEL assay and Hoechst staining were employed to detect apoptosis. pORF5 sensitized HeLa cells to autophagy that was induced by nutrient deprivation. In addition, pORF5 increased the ratio of LC3-II/LC3-I and Beclin-1 expression, down-regulated the expression of Bax and Caspase-3 and up-regulated Bcl-2 expression to suppress apoptosis induced by TNF-α. Autophagy inhibitor 3-MA elevated apoptotic rate significantly in pORF5-HeLa cells. The study preliminarily confirms that plasmid protein pORF5 mediates the crosstalk between autophagy and apoptosis, which may contribute to persistent C. trachomatis infection in host cells.